A Debreceni Tudományegyetem Orvostudományi Karának tansegédszemélyzete 1919–1950 III. rész: Klinikák 2. - Mudrák, József (Gerundium, 2012)
The Assista nt Personnel of the School of Medicine, University of Debrecen, 1919–1950. Part 3: The Clinics 2. Indispensable participants of the teaching and therapeutic activities of the School of Medicine were the personnel assisting the work of the professors. The register is designed to serve as an overall recording of the pertinent data of the departmental professors, assistant professors, instructors, interns, and teaching assistants. In this third part, the assistant personnel of the following clinics is registered: Clinic of Internal Medicine, Clinic of Surgery, Clinic of Otolaryngology, Polyclinic of Stomatology; and other institutes: University Pharmacy, the X-Ray Institute, the Institute and School of Nursery.